Collaborative Innovation Mechanism of Water Pollution Control Industry Chain Based on Complex Scientific Management - Quan Yuan; Ting Peng; Junren Ming (Discrete Dynamics in Nature and Society)
In the process of collaborative innovation of water pollution control industry chain, there are some problems, such as chain break and lack of chain, which lead to poor effect of water pollution collaborative governance and low economic benefits. Therefore, this paper proposes a research method of collaborative innovation mechanism of water pollution treatment industry chain based on complex scientific management. In view of the problems existing in the current industrial chain of water pollution control, the collaborative economic model and matter-element extension model of the industrial chain of water pollution treatment are constructed to improve the synergy effect of each link in the industrial chain and solve the contradictions of each link in the coordination process, so as to provide guarantee for the collaborative innovation of the industrial chain of water pollution control. The experimental results show that the proposed method can bring high economic benefits in the stage of source emission reduction, process interruption, and end treatment, and the water pollution treatment effect is good, which fully verifies the practical application effect of the method. After using the design method to purify, the maximum purification rate reaches more than 80%, and the purification effect reaches class v. The effect is remarkable, which has practical application value.